Museum specimens provide reliable SNP data for population genomic analysis of a widely distributed but threatened cockatoo species. (19th September 2019) - Ewart, Kyle M.; Johnson, Rebecca N.; Ogden, Rob; Joseph, Leo; Frankham, Greta J.; Lo, Nathan
Abstract: Natural history museums harbour a plethora of biological specimens which are of potential use in population and conservation genetic studies. Although technical advancements in museum genomics have enabled genome‐wide markers to be generated from aged museum specimens, the suitability of these data for robust biological inference is not well characterized. The aim of this study was to test the utility of museum specimens in population and conservation genomics by assessing the biological and technical validity of single nucleotide polymorphism (SNP) data derived from such samples. To achieve this, we generated thousands of SNPs from 47 red‐tailed black cockatoo ( Calyptorhychus banksii ) traditional museum samples (i.e. samples that were not collected with the primary intent of DNA analysis) and 113 fresh tissue samples (cryopreserved liver/muscle) using a restriction site‐associated DNA marker approach (DArTseq ™ ). Thousands of SNPs were successfully generated from most of the traditional museum samples (with a mean age of 44 years, ranging from 5 to 123 years), although 38% did not provide useful data. These SNPs exhibited higher error rates and contained significantly more missing data compared with SNPs from fresh tissue samples, likely due to considerable DNA fragmentation. However, based on simulation results, the level of genotyping error had a negligible effect on inference of population structure in this species. We did identify a bias towards low diversity SNPs in older samples that appears to compromise temporal inferences of genetic diversity. This study demonstrates the utility of a RADseq‐based method to produce reliable genome‐wide SNP data from traditional museum specimens.